“De Gaulle, ce grand guerrier toubab” ou résistance et domestication dans Monnè, outrages et défis d’Ahmadou Kourama - Lievois, Katrien (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
The colonization of the Americas, Asia, and Africa could not have occurred without interpreters, both native and colonial. (Venuti 1998: 158)This article uses some of the key concepts proposed by Lawrence Venuti to denounce the invisibility of translations and translators, to analyze the char-acter of the interpreter (and his very personal views on ‘resistance’ in poli- tics and translation) in Ahmadou Kourouma ’s Monnè, outrages et défis (1990), as well as those passages in the novel that put the French and Malinké languages into contact with each other. Indeed, the Ivorian author demonstrates how fuzzy the border between Venuti ’s concepts of domesticating and foreignizing translation can prove to be. Both linguistic and cultural displacements undermine the idea of a unified speaking subject, and the text, which is often ironic, raises questions about identity, literary nationality, linguistic geography and ideological convictions.